Application technology in coffee (Coffea arabica L.): effect of air assistance with manually driven equipment - Ruas, João Miguel Francisco; Oliveira, Gustavo Migliorini de; Araújo, Augusto Guilherme de; Balan, Rafael; Higashibara, Leandro Ryiuiti; Abi Saab, Otavio Jorge Grigoli (Semina: Ciências Agrárias, 2013)
Small farmers in various parts of Brazil, based the application of pesticides exclusively by a coastal manual sprayers. How it is simple equipment, there are few resources available to improve the quality of the application. The aim of this paper was to study the effect of air assistance, with manual override, in the deposition and percentage of coverage applied on the leaves of coffee plants, situated internally and externally. The equipment consisted of a sprayer coastal pressurized by CO2 attached to an air assistance equipment. At the exit of air assistance equipment a hose was adapted for driving the air flow emitted to the nozzle of the sprayer coastal (XR 110-02, expanded jet plane). It was used a solution of water + potassium chloride + fluorescent dye to the application. The levels of deposits were measured by electrical conductivity of the solution from the washing leaves and the percentage of coverage by ultraviolet light. The deposition was higher in leaves positioned externally to the plant, as well as the coverage percentage. The percentage of coverage was greater for the adaxial side of the coffee leaves. There was no difference for the use or not of the air assistance. Improvements in the generation and distribution of air in manually equipments may be necessary, in order to improve its use in the application of spray liquids.